Resolution of tremor associated with brainstem arachnoid cyst following surgical intervention: A case report - Andrey Rostislavovich Sitnikov; Rezida Maratovna Galimova; Dmitriy Konstantinovich Krekotin (Interdisciplinary Neurosurgery)
Introduction: Intracranial arachnoid cysts located in the brainstem are extremely rare. Neurological symptoms usually depend on the location of the cyst and present with varying degrees of motor deficit and cranial nerve palsy. Our case report describes the successful surgical treatment of an intraparenchymal brainstem arachnoid cyst followed by significant improvement of severe disabling contralateral tremor. Case presentation: A 34-year-old man was admitted to our clinic with a two-year history of progressive disabling right-sided tremor and muscle weakness. Neurological examination on admission showed moderate left-sided blepharoptosis, right-sided hemiparesis (MRC grade 4 strength) and severe right-sided kinetic and postural tremor. MRI showed a large multiseptal cystic lesion within the left cerebral peduncle and left part of the midbrain. The patient underwent surgical fenestration of the cyst via a left supracerebellar infratentorial approach in the semi-sitting position. The postoperative course was uneventful with significant reduction of tremor and hemiparesis on the second postoperative day. Follow-up MRI at 3 and 12 months showed reasonable reduction in the size of the cystic lesion and restoration of brainstem anatomy. The patient’s tremor decreased by 70 % according to the Tremor Research Group Essential Tremor Rating Scale (TETRAS scale). Conclusion: In cases of intraparenchymal cystic lesions presenting with neurological abnormalities, surgical exploration and fenestration of the lesion may be a safe treatment option with a good functional outcome.